Saudi Arabia’s Nursing Digitalization Journey: A Systematic Review - Bomuzah, Hussain Ali; Hzazi, Haifa Abdullah; Alharbi, Ohoud Ayesh; Towhari, Zahra Ali Ali; Kadomy, Amnah Yahia; Gofashi, Ohood Mdayish; Gohal, Wafa Ali Yahia; Alruwaili, Majedah Awad; Ghomari, Ezziah Yahya Hussin; Mjammy, Shagraa Ahmad Hassan; et al. (Journal of Posthumanism, 2025)
Background: Saudi Arabia’s Vision 2030 aims to revolutionize its healthcare system by integrating digital health technologies such as telemedicine, electronic health records (EHRs), and mobile health applications. These tools are expected to improve patient care, enhance nursing practices, and increase healthcare efficiency. However, despite the promise of digital health, challenges related to infrastructure, workforce training, and regulatory frameworks persist. Aim: This systematic review examines the impact of digital health technologies on nursing care, patient outcomes, and healthcare delivery in Saudi Arabia. It aims to evaluate the effectiveness, challenges, and future potential of these technologies under the Vision 2030 healthcare transformation. Method: A comprehensive literature search was conducted across multiple electronic databases (PubMed, Scopus, Web of Science, and Google Scholar) for studies published between 2021 and 2025. Ten primary articles were selected based on their relevance to digital health adoption in Saudi Arabia’s healthcare system. Data were synthesized from quantitative, qualitative, and mixed-methods studies. Results: The review identified several positive impacts of digital health tools, including improved healthcare access, better care coordination, and increased patient engagement. Telemedicine was particularly beneficial for rural populations, while EHRs facilitated enhanced communication among healthcare providers. Mobile health applications demonstrated significant improvements in chronic disease management. However, challenges such as limited infrastructure, regulatory barriers, and the need for workforce training were also highlighted. Conclusion: Digital health technologies have the potential to significantly improve nursing care and healthcare delivery in Saudi Arabia. Overcoming infrastructure and regulatory challenges, along with investing in workforce training, will be key to realizing the full potential of these technologies under Vision 2030.